Acupuncture Treatment of Diplopia Associated with Abducens Palsy: A Case Report. Issue 4 (July 2014) - Do, Alexander; Wahner-Roedler, Dietlind L.; Bauer, Brent A.
Abducens palsy (ie, sixth nerve palsy) is the most common single extraocular muscle palsy. The primary symptom is double vision. The treatment goal is to correct the underlying cause. If no cause is identified or the palsy is related to a well-managed chronic disease, treatment consists of patching one eye or applying a temporary prism. We report a patient whose abducens palsy resolved with four acupuncture treatments. The patient, a 58-year-old Vietnamese man with diabetes mellitus, presented to our institution's ophthalmology department with sudden onset of double vision. Ophthalmologic examination resulted in diagnosis of isolated left abducens palsy. The patient received a temporary prism for symptomatic relief. With no improvement after 2 months, he presented to our integrative medicine program inquiring about acupuncture. He received four acupuncture treatments over 11 weeks with complete resolution of his diplopia. This case is suggestive that acupuncture may be helpful treatment of patients with abducens palsy.